Mindfulness is associated with reduced barriers to exercise via decreasing psychological distress in help‐seeking young adults: A cross‐sectional brief report. Issue 9 (25th November 2021) - Dash, Sarah; Bourke, Matthew; Parker, Alexandra G.; Trott, Emma; Pascoe, Michaela C.
Abstract: Aim: Mental illness is common among young people. Exercise has benefits for mental health; however, young people experience a range of barriers to engaging in physical activity, one of which is psychological distress. Mindfulness is a modifiable factor that can reduce distress and may, in turn, reduce perceived barriers to physical activity. The aim of this work was to explore associations between dispositional mindfulness, psychological distress and barriers to engaging in physical activity. Methods: We used cross‐sectional survey data from young adults aged 15–25 years who attended youth mental health services (headspace centres). Demographic, mindfulness, exercise barriers and wellbeing data were collected. Results: Mediation analysis showed that greater dispositional mindfulness reduced perceived barriers to exercise via reductions in psychological distress among 88 help‐seeking young Australians. Conclusion: Interventions to increase dispositional mindfulness may be helpful in reducing psychological distress and lessening barriers to exercise engagement, therefore promoting mental health among young people experiencing mental health symptoms.